Understanding functional abdominal pain disorders among children: a multidisciplinary expert consensus statement - Vandenplas, Yvan; Darma, Andy; Indrio, Flavia; Aw, Marion; Vieira, Mario C.; Vivatvakin, Boosba; Treepongkaruna, Suporn; Cruchet, Sylvia; Acharyya, Bhaswati C.; Vázquez, Rodrigo; Yeung, Chun Yan; Gutiérrez, Pedro (Frontiers in Pediatrics, 2025)
IntroductionFunctional abdominal pain disorders (FAPDs) are pediatric gastrointestinal conditions marked by chronic or recurrent abdominal pain without anatomical and/or biochemical abnormalities. This position paper guides primary care providers in the early diagnosis and management of FAPDs to improve the well-being of affected children and their families.MethodsA 12-member expert advisory board reviewed current approaches to diagnosing and managing FAPDs in children. Based on literature and discussions, 23 statements were drafted and voted on to achieve an acceptable level of agreement.ResultsFirst-line healthcare professionals are key in diagnosing FAPDs, using ROME diagnostic criteria and recognizing red flags for accurate assessment and referrals. Comprehensive evaluation, including medical, dietary, and psychosocial history, physical exams, and basic tests helped to identify the initial triggers. Probiotics such as Limosilactobacillus (L. reuteri) DSM 17938 and Lacticaseibacillus rhamnosus (L. rhamnosus) help in alleviating functional abdominal pain (FAP) in children along with primary measures, such as dietary modifications [a balanced diet advocating moderation in fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP)-rich foods] and physical activity. Probiotics should be given for 6–8 weeks and can be resumed if symptoms recur. Cognitive-behavioral and hypnotic therapy also help, with remote options such as web-based, compact disk (CD)-based or application-based tools available.DiscussionThis position paper provides expert insights to guide primary care providers in diagnosing and managing FAPDs, equipping them to make informed decisions for effective management of FAPDs.